Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12302-020-00390-x
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis kinetic modelling of abundant plastic waste (PET) and in-situ emission monitoring

Abstract: Background: Recycling the ever-increasing plastic waste has become an urgent global concern. One of the most convenient methods for plastic recycling is pyrolysis, owing to its environmentally friendly nature and its intrinsic properties. Understanding the pyrolysis process and the degradation mechanism is crucial for scale-up and reactor design. Therefore, we studied kinetic modelling of the pyrolysis process for one of the most common plastics, polyethylene terephthalate (PET). The focus was to better unders… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 47 publications
5
54
0
1
Order By: Relevance
“…Although some product was collected, a yield of only about 52% was obtained. Osman et al have reported that, depending on process conditions (like heat rate), PET pyrolysis can already start below 350 °C [ 49 ]. PET pyrolysis can result in many different products, including terephthalic acid, which is suspected to be a reason for piping clogging [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although some product was collected, a yield of only about 52% was obtained. Osman et al have reported that, depending on process conditions (like heat rate), PET pyrolysis can already start below 350 °C [ 49 ]. PET pyrolysis can result in many different products, including terephthalic acid, which is suspected to be a reason for piping clogging [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ICTAC recommendation on kinetic data gathering and processing were largely followed with at least an order of magnitude difference between the least and the highest heating rate. Furthermore, to ensure reproducibility and accuracy of the TGA data the heating rate at 20 °C/min was repeated 18 .…”
Section: Methodsmentioning
confidence: 99%
“…This obviates the need for the inclusion of a decomposition model in the rate equation and thus, relatively, simplifies the determination of the kinetic parameters. However, it requires multiple TGA measurements at a minimum of four different heating rates 18 . Vyazovkin et al 19 recommended that the difference between the lowest and highest heating rate should be at least an order of magnitude—starting with a very low heating rate (e.g., 2.5 °C/min).…”
Section: Introductionmentioning
confidence: 99%
“…7 The main model-free methods discussed in the literature include ASTM-E698, which is a model-free noniso-conversional approach, the Flynn-Wall and Ozawa (FWO), and Kissinger-Akahira-Sunrose (KAS), which are categorized as integral iso-conversional methods, and the Friedman method which is a differential iso-conversional method. [6][7][8][9][10][11][12][13] The main issue related to the ASTM-E698 method is that a single activation energy value is calculated, not considering reaction progress in such a complex thermochemical process. It is more suitable for a single-step reaction.…”
Section: Introductionmentioning
confidence: 99%